The development of interactive magic card (IMC) based on flash card - Abdul Muhith; Ulfa Wulan Agustina; Yuyun Bahtiar; Nurul Afidah (Universitas Islam Malang, 2020)
Researchers aim to develop Interactive Magic Card as a medium that is suited to learning needs. There are 2 objectives in this study; 1) developing Interactive Magic Card as a learning medium; 2) find out the feasibility of the media. This research uses the Research and Development method which was adapted from Borg and Gall. This English learning media is an HTML5-based Flash Card application that was developed to help students in mastering vocabulary and improve their Speaking and Writing skills.The results of this study indicate that; 1) the results of the material expert validation are 89; 2) the results of media expert validation are 84; 3) main field test results are 91. Based on the results of the study, the researchers concluded that Interactive Magic Cardis suitable for use as a medium for learning English.